Adsorption of Aun (n = 1–4) clusters on Fe3O4(001) B-termination1. Issue 56 (19th June 2015) - Yu, Xiaohu; Zhang, Xuemei; Wang, Shengguang; Feng, Gang
<x xml:space="preserve">Abstract</x> The adsorption of Aun (n = 1–4) clusters on stoichiometric, reduced and hydrated Fe3O4(001) B-terminations were studied using the GGA density functional theory including the Hubbard parameter (U) to describe the on-site Coulomb interaction.